THE FUZZY SACREDNESS AURA AND CYBER-BASED DA’WAH: Redrawing Karamah of Tuan Guru within The Belief System of Sasak Muslims (State Islamic University (UIN) of Sunan Ampel Surabaya, 2020)
This article examines Sasak Muslims’ belief in tuan guru’s karamah (charisma) in the midst of the emerging trend of cyber da‘wah. Findings illustrate that Sasak Muslims have repeatedly recognized that tuan guru’s charisma becomes an important consideration for their respect and obedience to ‘ulama and are of great significance for da'wah. Accordingly, they have remained in favour of lived-da‘wah practices compared to the online ones. There are two facets that frame the underlying rationales of the findings. First, not all Islamic rituals and da‘wah activities can be transformed into the digital realm because da‘wah has complexity of concepts and meanings embedded within any Islamic rituals that would be difficult to be reproduced into internet medium. Second, da’wah through digital platforms lead people to feel less auratic experience as normally they can through in-person da‘wah activities.